2013
DOI: 10.1007/s11910-013-0384-x
|View full text |Cite
|
Sign up to set email alerts
|

Poor Oral Health as a Chronic, Potentially Modifiable Dementia Risk Factor: Review of the Literature

Abstract: Poor oral health, including caries, tooth loss, and periodontitis, is ubiquitous worldwide, and is potentially treatable and preventable. Like adverse oral health conditions, Alzheimer disease and related disorders are also very common among aging populations. Established risk factors for Alzheimer disease include cerebrovascular disease and its vascular risk factors, many of which share associations with evidence of systemic inflammation also identified in periodontitis and other poor oral health states. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
126
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 121 publications
1
126
0
3
Order By: Relevance
“…Oral bacteria and their virulence factors affect the central nervous system pathology [13,14], and indiscriminate release of inflammatory mediators cause neuronal injury [5,[15][16][17]. The host's humoral responses to periodontal pathogen infections are ineffective, but if combined with other tests, they may prove useful as predictive biomarkers of AD [18][19][20]. The failure of Baumgart et al [2] to recognise these facts prompted a response in the form of a letter to the Editor by Kamer et al [21].…”
Section: Making a Case For Periodontitis As A Risk Factor For Alzheimmentioning
confidence: 99%
“…Oral bacteria and their virulence factors affect the central nervous system pathology [13,14], and indiscriminate release of inflammatory mediators cause neuronal injury [5,[15][16][17]. The host's humoral responses to periodontal pathogen infections are ineffective, but if combined with other tests, they may prove useful as predictive biomarkers of AD [18][19][20]. The failure of Baumgart et al [2] to recognise these facts prompted a response in the form of a letter to the Editor by Kamer et al [21].…”
Section: Making a Case For Periodontitis As A Risk Factor For Alzheimmentioning
confidence: 99%
“…Inflammation, blood vessel damage, and oxidative stress play an important role in the etiopathogeny of AD, 6 leading to the hypothesis that periodontitis may be associated with cognitive impairment and dementia 7 . Periodontitis is a local infectious/inflammatory process with potential systemic effects, and the mechanisms mediated by periodontopathogenic microorganisms and the inflammation they activate may explain the initial vascular damage and repercussions at both the cardiovascular 8 and cerebral 9 levels. There is increasing evidence that periodontitis may be a modifiable risk factor for cardiovascular disease, 10‐13 but its association with dementia or cognitive impairment is less clear.…”
mentioning
confidence: 99%
“…Another investigation of healthy patients reported that tissues affected by periodontitis may be a source of peripheral Aβ18, whose production by platelets or skeletal muscle cells has also been demonstrated 19 . However, it remains unclear whether these findings are truly related and might explain the association observed between periodontal disease and cognitive impairment, especially because of the numerous potential confounders that should be controlled for, including age, sex, poor oral hygiene, tooth loss, or systemic factors such as diabetes mellitus, dyslipidemia, hypertension, or tobacco or alcohol consumption 20 . The hypothesis of the present study is that periodontitis may increase accumulation and deposit of Aβ peptides in the brain and thereby favor development of dementia.…”
mentioning
confidence: 99%